Modelo de apoio à decisão para seleção de biomassas da pecuária e tipos de biodigestores com abordagem multicritério - Seabra Júnior, Edward (2022)
Biomass is any organic material that, through biotechnological processes, is decomposed into two basic products: biofertilizer and biogas. Biogas is an important source of renewable energy, resulting from the technology of anaerobic digestion used in the use of biomass and can be used for various purposes such as: simple burning, cogeneration, heating, motor drive, biofuels and even electricity generation. There are three basic steps that are interrelated in the process as a whole, they are: biomass selection; biodigester selection; selection of the purpose for using the biogas. Within each stage, the person responsible for the project needs to make complex decisions, at the risk of making the project technically unfeasible if a choice is made wrongly, increasing costs, not producing quality biogas, not being able to leave the organic matter inert for some sizing error. This time, the objective of this study was to propose a methodological procedure for decision support with sequential, iterative steps and with the support of multicriteria methods, in order to provide technical support to the decision maker with a view to solving problems of biomass selection and types of biodigesters. The results obtained through the application of the methodology were carried out in two case studies and demonstrated that, from the application, it was possible to obtain consistent answers both for the selection of biomasses and for the selection of the type of biodigesters confirmed by the sensitivity analysis.